Cover Image - Vanasse, Thomas J. (Hum Brain Mapp, 2018)
[Image: see text] COVER ILLUSTRATION The cover‐art references the research article, ‘BrainMap VBM: An environment for structural meta‐analysis.’ (Top) The word‐cloud corresponds to the current data volume (per diagnosis) of voxel‐based morphometry experiments in the newly expanded database, BrainMap VBM. (Middle) To analyze the database en masse, coordinates from >2,000 experiments were grouped together and smoothed to model atrophy. (Bottom) Independent Component Analysis (ICA) was applied to extract networks of structural covariance related to disease.